Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Microbial carbon use efficiency is governed by site-level soil and climate factors and does not explain soil carbon gains under diversified crop rotations - Timothy M. Bowles; Maria Mooshammer; A. Stuart Grandy; Kevin Geyer; Serita D. Frey; Francisco Calderón; Steve Culman; Bill Deen; Kari Dunfield; Virginia L. Jin; R. Michael Lehman; Shannon L. Osborne; et al. (Soil Biology and Biochemistry, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

Effects of duration of a plant-based diet stimulus at first feeding on nutritional programming in Atlantic salmon (Salmo salar) - Xu Gong; Matthew Sprague; Stuart McMillan; Pedro Gómez-Requeni; Fernando Norambuena; Sam A. M. Martin; Douglas R. Tocher; Mónica B. Betancor (Fish Physiology and Biochemistry, 2026)
Nutritional programming could potentially be a strategy for sustainable aquaculture to adapt fish to feeds formulated with low levels of marine ingredients. The present study examined the effects of early dietary stimulus duration and the impacts of a later challenge with a similar diet. At first feeding, Atlantic salmon ( Salmo salar ) fry of ~ 0.15 g initial weight were fed a vegetable diet (77% plant-based ingredients) for either 1 (V1) or 2 weeks (V2), while a control group (M) received a marine diet (86% marine-based ingredients) for the 2 weeks (stimulus phase). All fish then received a marine diet for 16 weeks (intermediate phase) before being refed a vegetable diet for 6 weeks (challenge phase). Water temperature was 13 °C during the trial, and the only difference between the three experimental groups (V1, V2 and M) was their dietary regime during the first 2 weeks. Obviously, stimulus duration had no phenotypic impacts on growth or tissue fatty acid compositions of either total or polar lipids after challenge. However, the expressions of key genes of LC-PUFA biosynthesis were upregulated significantly in the V1 group, whereas the expressions of most transcription factors were downregulated in the V2 group. After the challenge, the circular muscle thickness of the intestine in the V1 group was increased by 15%, and goblet cell numbers were reduced by 15%. Overall, further investigations about the duration of the stimulus and assessment with longer challenges are required to elicit positive effects and to refine the use of nutritional programming in Atlantic salmon.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Mapping area of habitat for inland wetland species - Francesca A. Ridley; Catherine A. Sayer; Louise Mair; Daniele Baisero; Monika Böhm; Thomas M. Brooks; Stuart H. M. Butchart; Viola Clausnitzer; Jeorg Freyhof; Günther Grill; Ian Harrison; Randall R. Jiménez; et al. (Conservation Biology, 2026)
Area of habitat (AOH) maps provide a high‐resolution representation of the habitat available in a species’ range and can support conservation policy and planning processes. However, until recently, there was insufficient knowledge on the distribution of inland wetlands and freshwater biodiversity to develop AOH mapping methods specifically tailored to inland wetlands. We used a combined empirical and thematic approach to translate inland wetland habitat classes in the International Union for Conservation of Nature (IUCN) Habitats Classification Scheme into spatially explicit wetland‐cover types derived from the Global Lakes and Wetlands Database 2 and the World Karst Aquifer Map. The AOH was subsequently estimated as the area in the mapped range that corresponded to each species’ habitat and elevation associations. We developed and tested the method with IUCN Red List assessment data, range maps, and point locality data for fishes, odonates, decapod crustaceans, and mollusks (22,876 species). The method performed well in comparison with similar methods already developed for terrestrial mammals, birds, amphibians, and reptiles. The mean map prevalence (proportion of area in a species’ range that was AOH) was 18–32% for each taxonomic group. Based on data on known localities of occurrence, 78–100% of species per taxonomic group had a higher classification accuracy than expected if AOH were distributed in the range at random. This represents an increased accuracy in the distribution of wetland species. Our study represents the first attempt to distinguish between inland wetland habitat subclasses and to include subterranean habitats in an AOH mapping method. Our method will facilitate the inclusion of previously underrepresented taxa in key conservation tools and analyses and is expected to increase the accuracy of AOH mapping for any species associated with inland wetlands.

Managing range-shifting, competing species in marine reserve networks: the importance of reserve configuration and transient dynamics in age-structured populations - Alicia M. Cheripka; Stuart R. Borrett; J. Wilson White (Theoretical Ecology, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Effect of a cognitive behavioural therapy intervention to improve sleep on food preferences: A randomized controlled trial in adults with overweight and obesity - Ayan M. Merchant; Stuart R. Gray; Cindy M. Gray; Graham Finlayson; Anthony M. Manyara; Maria F. Gabler Trisotti; Jason M.R. Gill (Appetite, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

The impact of neotectonics on the geomorphology of the northern Great Barrier Reef - Atefeh Sansoleimani; Gregory E. Webb; Daniel L. Harris; Stuart R. Phinn; Chris M. Roelfsema (Coral Reefs, 2025)
The Great Barrier Reef (GBR) is assumed to be a tectonically stable area, but recent studies show that neotectonic activity could have affected the geomorphology and evolution of the coral reefs. We used bathymetry, free-air gravity and 2D seismic data to test the hypothesis that neotectonic (i.e. geologically recent or currently active) faults have affected the morphology and major aspects of reefs’ growth in the northernmost zone of the GBR, 13.5°S–10.5° S. Bathymetry data show that elongated reef platforms, oriented WNW-ESE, are systematically deflected at their ends or, in some cases, offset through their bodies, along interpreted structural lineaments. Submarine stream channels, running mostly in WNW-ESE orientations, have deepened their courses within the areas occupied by elongated platforms. The deflection or offset of the coral reefs is interpreted to result from movement on neotectonic faults based on the following lines of evidence: (1) fault lineaments based on reef platform morphology are almost parallel to those interpreted from free-air gravity data, consistent with deep-seated faults; (2) offsets along the deflected zones of reef platforms are oriented sub-parallel to interpreted fault lineaments, consistent with those faults having deformed reef morphology since reef initiation; (3) some inferred fault positions correspond to faults interpreted from limited 2D seismic reflection data; (4) fluvial incision of the continental shelf between elongated reefs is consistent with neotectonic fault activity; and (5) M > 4 earthquakes have been recorded adjacent to some interpreted lineaments. We propose that the GBR has been affected by localised active tectonism in different ways. Small, localised faults active in the late Pleistocene displaced and deflected coral reefs laterally in the northernmost zone of the GBR. In the central zone of the GBR larger (NNE-SSW trending) bounding faults controlled regional subsidence, thus affecting accommodation and broader reef growth patterns. Our results suggest that recently active faults in the GBR have had, and may continue to have, important ramifications for the developmental history of the reef province. These findings are significant given that the assumption of tectonic stability underpins many interpretations of the potential effects of changing climate and sea level on reef growth.

Genome-wide association for precocial maturation in juvenile male Spring Chinook salmon (Oncorhynchus tshawytscha) - Nick F. Hoffman; Stuart C. Willis; Hayley M. Nuetzel; Andrew L. Pierce; James J. Nagler; Shawn R. Narum (Conservation Genetics, 2025)
Fish conservation through hatchery supplementation involves maintaining population structure similar to natural populations. High proportions of precociously mature two-year-old male Chinook salmon (i.e. minijacks) observed in hatchery populations reduces the number of anadromous males in the population. Understanding the genetic architecture of this trait could be used to adjust hatchery practices to reduce precocious maturation. The genetic control of this trait was examined in a hatchery population of Columbia River Spring Chinook salmon over two replicate year classes (brood years BY2018 and BY2019). Genome wide allele frequencies from millions of single nucleotide polymorphisms (SNPs) were compared between immature males and minijacks identified by plasma 11-ketotestosterone levels. Genome scans identified 1,917 SNPs within and between brood years. Within brood years, there were two and four notable peaks of significance in BY2018 and BY2019, respectively. Combining the same phenotypes between brood years resulted in candidate regions on multiple chromosomes associated with precocial maturation as a minijack. The strongest signals from the combined year analysis were on chromosomes 15 (617 SNPs, five genes) and 18 (922 SNPs, nine genes). Individuals representing the extreme ends of the phenotypic distributions had notable signals on chromosomes 17 and 18, which have been previously identified as age-of-maturity candidates in this species. These analyses indicated that genetic control of minijack maturation is influenced by many regions of small effect including markers that may be sex-linked on chromosomes 17 and 18. The regions identified in this study will aid in conservation and broodstock monitoring relating to abundances of minijacks in hatchery origin populations.

Sugarcane (Saccharum spp. hybrids) biotechnology research in South Africa - Sandra J. Snyman; Aimee C. Koch; Robyn M. Jacob; Shailesh V. Joshi; Sharon A. McFarlane; Christell van der Vyver; R. Stuart Rutherford (In Vitro Cellular & Developmental Biology - Plant, 2025)
Commercial sugarcane, Saccharum spp. hybrids, arose from interspecific crossing in the late 1890s and the resultant complex polyploid genome has challenged conventional breeding approaches. The grower- and miller-funded South African Sugarcane Research Institute (SASRI) has a 100-yr history which began by breeding for local agroclimatic regions. Biotechnology for cultivar improvement was introduced in the early 1990s. Collaborations with local research institutes and the International Consortium for Sugarcane Biotechnology (ICSB) have enabled advances such as the genome sequence being published this year, signifying a real opportunity to implement bioinformatic and marker techniques for targeted cultivar enhancement. This review focuses on biotechnology-related interventions that have supported sugarcane research and resulted in SASRI-bred N cultivars being widely grown in many sub-Saharan African sugarcane-growing countries.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Soil Carbon Saturation: What Do We Really Know? - Katerina Georgiou; Denis Angers; Ryan E. Champiny; M. Francesca Cotrufo; Matthew E. Craig; Sebastian Doetterl; A. Stuart Grandy; Jocelyn M. Lavallee; Yang Lin; Emanuele Lugato; Christopher Poeplau; Katherine S. Rocci; et al. (Global Change Biology, 2025)
Managing soils to increase organic carbon storage presents a potential opportunity to mitigate and adapt to global change challenges, while providing numerous co‐benefits and ecosystem services. However, soils differ widely in their potential for carbon sequestration, and knowledge of biophysical limits to carbon accumulation may aid in informing priority regions. Consequently, there is great interest in assessing whether soils exhibit a maximum capacity for storing organic carbon, particularly within organo–mineral associations given the finite nature of reactive minerals in a soil. While the concept of soil carbon saturation has existed for over 25 years, recent studies have argued for and against its importance. Here, we summarize the conceptual understanding of soil carbon saturation at both micro‐ and macro‐scales, define key terminology, and address common concerns and misconceptions. We review methods used to quantify soil carbon saturation, highlighting the theory and potential caveats of each approach. Critically, we explore the utility of the principles of soil carbon saturation for informing carbon accumulation, vulnerability to loss, and representations in process‐based models. We highlight key knowledge gaps and propose next steps for furthering our mechanistic understanding of soil carbon saturation and its implications for soil management.

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

New Zealand Myrtaceae are susceptible to a strain from the Eucalyptus biotype of Austropuccinia psidii present in South America - Julia Soewarto; Carlos Pérez; Michael Bartlett; Chanatda Somchit; Beccy Ganley; Roanne Sutherland; Sofía Simeto; Jane E. Stewart; Jorge R. Ibarra Caballero; Stuart Fraser; Peter M. Scott; Jayanthi Nadarajan; et al. (Biological Invasions, 2025)
The international spread of the myrtle rust pathogen, Austropuccinia psidii , can be largely attributed to the “pandemic” biotype that has more than 450 host species. However, within South America, the putative native range of A. psidii , multiple biotypes have been characterised, each with a restricted known number of hosts. These biotypes may pose a significant biosecurity threat to countries already affected by the pandemic biotype. Here, we report the susceptibility of four species of Myrtaceae from New Zealand, pōhutukawa ( Metrosideros excelsa ), mānuka ( Leptospermum scoparium ), kānuka ( Kunzea ericoides ), and rawiri mānuka ( Kunzea ericoides ‘gumland ecotype’), to a strain of the Eucalyptus biotype of A. psidii . Symptoms and signs developed on inoculated plants of all species. Qualitative resistance phenotypes, with no disease development, were observed for all four species. However, no hypersensitive responses were observed. As seen for other biotypes, pōhutukawa had the greatest susceptibility, while kānuka had the lowest. These findings are consistent with prior work, showing that the Eucalyptus biotype can infect a broader range of species than its field host association implies. As well as uredinia (asexual spores), telia (sexual spores) developed on several plants, indicating that these species could provide a universal host for sexual reproduction and outcrossing between biotypes. Knowledge that the Eucalyptus biotype of A. psidii is virulent on several indigenous New Zealand Myrtaceae will inform future biosecurity risk assessments. These findings highlight the need to develop diagnostics tools to differentiate between biotypes and allow rapid responses to potential future incursions.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Associations between MASLD, atrial fibrillation, cardiovascular events, mortality and aspirin use in older adults - Daniel Clayton-Chubb; Stuart K. Roberts; Ammar Majeed; Robyn L. Woods; Andrew M. Tonkin; Mark R. Nelson; Andrew T. Chan; Joanne Ryan; Cammie Tran; Alexander Hodge; John S. Lubel; Hans G. Schneider; et al. (GeroScience, 2024)

Smartphone-based hyperspectral imaging for ice sheet and proglacial applications in South-West Greenland - M.B. Stuart; M. Davies; C. Fisk; E. Allen; A.J. Sole; R. Ing; M.J. Hobbs; J.R. Willmott (Science of The Total Environment, 2024)

Annotation of DOM metabolomes with an ultrahigh resolution mass spectrometry molecular formula library - Nicole R. Coffey; Christian Dewey; Kieran Manning; Yuri Corilo; William Kew; Lydia Babcock-Adams; Amy M. McKenna; Rhona K. Stuart; Rene M. Boiteau (Organic Geochemistry, 2024)

The many ages of Triton: New crater counts on the Voyager high-resolution image sequence and implications for impactor provenance - William B. McKinnon; Kelsi N. Singer; Stuart J. Robbins; Michelle R. Kirchoff; Simon B. Porter; Paul M. Schenk; Ted Stryk; Jeffrey M. Moore (Icarus, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Exome variant prioritization in a large cohort of hearing-impaired individuals indicates IKZF2 to be associated with non-syndromic hearing loss and guides future research of unsolved cases - Hedwig M. Velde; Maryam Vaseghi-Shanjani; Jeroen J. Smits; Gayatri Ramakrishnan; Jaap Oostrik; Mieke Wesdorp; Galuh Astuti; Helger G. Yntema; Lies Hoefsloot; Cris P. Lanting; Martijn A. Huynen; Anna Lehman; et al. (Human Genetics, 2024)
Although more than 140 genes have been associated with non-syndromic hereditary hearing loss (HL), at least half of the cases remain unexplained in medical genetic testing. One reason is that pathogenic variants are located in ‘novel’ deafness genes. A variant prioritization approach was used to identify novel (candidate) genes for HL. Exome-wide sequencing data were assessed for subjects with presumed hereditary HL that remained unexplained in medical genetic testing by gene-panel analysis. Cases in group AD had presumed autosomal dominantly inherited HL (n = 124), and in group AR, presumed autosomal recessive HL (n = 337). Variants in known and candidate deafness genes were prioritized based on allele frequencies and predicted effects. Selected variants were tested for their co-segregation with HL. Two cases were solved by variants in recently identified deafness genes ( ABHD12 , TRRAP ). Variant prioritization also revealed potentially causative variants in candidate genes associated with recessive and X-linked HL. Importantly, missense variants in IKZF2 were found to co-segregate with dominantly inherited non-syndromic HL in three families. These variants specifically affected Zn 2+ -coordinating cysteine or histidine residues of the zinc finger motifs 2 and 3 of the encoded protein Helios. This finding indicates a complex genotype–phenotype correlation for IKZF2 defects, as this gene was previously associated with non-syndromic dysfunction of the immune system and ICHAD syndrome, including HL. The designed strategy for variant prioritization revealed that IKZF2 variants can underlie non-syndromic HL. The large number of candidate genes for HL and variants therein stress the importance of inclusion of family members for variant prioritization.

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

Intracerebral Administration of a Novel Self-Assembling Peptide Hydrogel Is Safe and Supports Cell Proliferation in Experimental Intracerebral Haemorrhage - Faye Bolan; Ben R. Dickie; James R. Cook; Josephine M. Thomas; Emmanuel Pinteaux; Stuart M. Allan; Alberto Saiani; Catherine B. Lawrence (Translational Stroke Research, 2024)
Intracerebral haemorrhage (ICH) is the deadliest form of stroke, but current treatment options are limited, meaning ICH survivors are often left with life-changing disabilities. The significant unmet clinical need and socioeconomic burden of ICH mean novel regenerative medicine approaches are gaining interest. To facilitate the regeneration of the ICH lesion, injectable biomimetic hydrogels are proposed as both scaffolds for endogenous repair and delivery platforms for pro-regenerative therapies. In this paper, the objective was to explore whether injection of a novel self-assembling peptide hydrogel (SAPH) Alpha2 was feasible, safe and could stimulate brain tissue regeneration, in a collagenase-induced ICH model in rats. Alpha2 was administered intracerebrally at 7 days post ICH and functional outcome measures, histological markers of damage and repair and RNA-sequencing were investigated for up to 8 weeks. The hydrogel Alpha2 was safe, well-tolerated and was retained in the lesion for several weeks, where it allowed infiltration of host cells. The hydrogel had a largely neutral effect on functional outcomes and expression of angiogenic and neurogenic markers but led to increased numbers of proliferating cells. RNAseq and pathway analysis showed that ICH altered genes related to inflammatory and phagocytic pathways, and these changes were also observed after administration of hydrogel. Overall, the results show that the novel hydrogel was safe when injected intracerebrally and had no negative effects on functional outcomes but increased cell proliferation. To elicit a regenerative effect, future studies could use a functionalised hydrogel or combine it with an adjunct therapy.

The Impact of Land Conversion on Primate Habitats: Refining the Extent of Occurrence Data for Four Capuchin Species in North and Northeastern Brazil - Anailda T. Farias; Stuart E. Hamilton; Luciana B. M. Pires; Gustavo R. Canale; Ricardo R. Santos; Andrea Presotto (International Journal of Primatology, 2024)
Conversion of primate forest habitat is a global concern with significant implications for primate populations. Although the geospatial Extent of Occurrence (EOO) data provided for primates by the International Union for the Conservation of Nature are widely used, they do not accurately reflect the existing extent of primate species because of ongoing habitat loss. We focused on four capuchin monkey species ( Sapajus apella , S. flavius , S, libidinosus , and S. xanthosternos ), all native to North and Northeastern Brazil, to prioritize research by the Capuchin Action Network. We refined the EOOs for the four primate species using MapBiomas land cover data. We accounted for areas of agriculture, urban, and mining and updated the EOOs of the four species. Additionally, we evaluated the Conservation Units in each EOO. Conservation Units are protected areas critical to mitigating habitat loss in Brazil. Our results show that S. apella has lost the smallest amount of its EOO (13%), while S. flavius has lost the most (77%). Agriculture was the leading cause of land cover change, followed by urbanization and mining. We provide an updated EOO for the four capuchin species and highlight the need for conservation efforts to address the challenges posed by human activities in the capuchin species’ habitats.

Assessing the global prevalence of wild birds in trade - Paul F. Donald; Eresha Fernando; Lauren Brown; Michela Busana; Stuart H. M. Butchart; Serene Chng; Alicia de la Colina; Juliana Machado Ferreira; Anuj Jain; Victoria R. Jones; Rocio Lapido; Kelly Malsch; et al. (Conservation Biology, 2024)
Trade represents a significant threat to many wild species and is often clandestine and poorly monitored. Information on which species are most prevalent in trade and potentially threatened by it therefore remains fragmentary. We used 7 global data sets on birds in trade to identify species or groups of species at particular risk and assessed the extent to which they were congruent in terms of the species recorded in trade. We used the frequency with which species were recorded in the data sets as the basis for a trade prevalence score that was applied to all bird species globally. Literature searches and questionnaire surveys were used to develop a list of species known to be heavily traded to validate the trade prevalence score. The score was modeled to identify significant predictors of trade. Although the data sets sampled different parts of the broad trade spectrum, congruence among them was statistically strong in all comparisons. Furthermore, the frequency with which species were recorded within data sets was positively correlated with their occurrence across data sets, indicating that the trade prevalence score captured information on trade volume. The trade prevalence score discriminated well between species identified from semi‐independent assessments as heavily or unsustainably traded and all other species. Globally, 45.1% of all bird species and 36.7% of globally threatened bird species had trade prevalence scores ≥1. Species listed in Appendices I or II of CITES, species with large geographical distributions, and nonpasserines tended to have high trade prevalence scores. Speciose orders with high mean trade prevalence scores included Falconiformes, Psittaciformes, Accipitriformes, Anseriformes, Bucerotiformes, and Strigiformes. Despite their low mean prevalence score, Passeriformes accounted for the highest overall number of traded species of any order but had low representation in CITES appendices. Geographical hotspots where large numbers of traded species co‐occur differed among passerines (Southeast Asia and Eurasia) and nonpasserines (central South America, sub‐Saharan Africa, and India). This first attempt to quantify and map the relative prevalence in trade of all bird species globally can be used to identify species and groups of species that may be at particular risk of harm from trade and can inform conservation and policy interventions to reduce its adverse impacts.

Environmental factors have stronger effects than biotic processes in patterns of intertidal populations along the southeast coast of Brazil - Cesar A.M.M. Cordeiro; André Pardal; Luis Giménez; Áurea M. Ciotti; Stuart R. Jenkins; Michael T. Burrows; Gray A. Williams; Ronaldo A. Christofoletti (Marine Environmental Research, 2024)

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Local elephant movements, turning angles, and water access across a rainfall gradient in Southern Africa - Jessica R. Bucciarelli; Stuart L. Pimm; Ryan M. Huang; Michael J. Chase; Keith Leggett; Armanda D. Bastos; Rudi J. van Aarde (Biological Conservation, 2024)

The new kid on the block in insect pest management: sprayable RNAi goes commercial - Junjie Yan; Ralf Nauen; Stuart Reitz; Andrei Alyokhin; Jiang Zhang; David Mota-Sanchez; Yonggyun Kim; Subba Reddy Palli; Silvia I. Rondon; Brian A. Nault; Juan Luis Jurat-Fuentes; Michael S. Crossley; et al. (Science China Life Sciences, 2024)

Novel estimation of African swine fever transmission parameters within smallholder villages in Lao P.D.R - Nina Matsumoto; Michael P. Ward; Tariq Halasa; Kathrin Schemann; Syseng Khounsy; Bounlom Douangngeun; Watthana Thepagna; Phouvong Phommachanh; Jarunee Siengsanan-Lamont; James R. Young; Jenny-Ann L. M. L. Toribio; Russell D. Bush; et al. (Tropical Animal Health and Production, 2024)
African Swine Fever (ASF) disease transmission parameters are crucial for making response and control decisions when faced with an outbreak, yet they are poorly quantified for smallholder and village contexts within Southeast Asia. Whilst disease-specific factors − such as latent and infectious periods − should remain reasonably consistent, host, environmental and management factors are likely to affect the rate of disease spread. These differences are investigated using Approximate Bayesian Computation with Sequential Monte-Carlo methods to provide disease parameter estimates in four naïve pig populations in villages of Lao People’s Democratic Republic. The villages represent smallholder pig farmers of the Northern province of Oudomxay and the Southern province of Savannakhet, and the model utilised field mortality data to validate the transmission parameter estimates over the course of multiple model generations. The basic reproductive number between-pigs was estimated to range from 3.08 to 7.80, whilst the latent and infectious periods were consistent with those published in the literature for similar genotypes in the region (4.72 to 6.19 days and 2.63 to 5.50 days, respectively). These findings demonstrate that smallholder village pigs interact similarly to commercial pigs, however the spread of disease may occur slightly slower than in commercial study groups. Furthermore, the findings demonstrated that despite diversity across the study groups, the disease behaved in a consistent manner. This data can be used in disease control programs or for future modelling of ASF in smallholder contexts.

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Conservation genomics of the threatened Trispot Darter (Etheostoma trisella) - Kayla M. Fast; Brook L. Fluker; Bernard R. Kuhajda; Patrick E. O’Neil; Stuart W. McGregor; Matthew S. Piteo; Michael W. Sandel (Conservation Genetics, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

The distribution of metal and petroleum-derived contaminants within sediments around oil and gas infrastructure in the Gippsland Basin, Australia - Sharon E. Hook; Scott Foster; Franziska Althaus; Douglas Bearham; Brad M. Angel; Andrew T. Revill; Stuart L. Simpson; Joanna Strzelecki; Tom Cresswell; Keith R. Hayes (Marine Pollution Bulletin, 2023)

Correction to: Global invasion history and native decline of the common starling: insights through genetics - Katarina C. Stuart; Natalie R. Hofmeister; Julia M. Zichello; Lee A. Rollins (Biological Invasions, 2023)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Systemic innate myeloid responses to acute ischaemic and haemorrhagic stroke - Ruth Stephens; John R. Grainger; Craig J. Smith; Stuart M. Allan (Seminars in Immunopathology, 2023)
Acute ischaemic and haemorrhagic stroke account for significant disability and morbidity burdens worldwide. The myeloid arm of the peripheral innate immune system is critical in the immunological response to acute ischaemic and haemorrhagic stroke. Neutrophils, monocytes, and dendritic cells (DC) contribute to the evolution of pathogenic local and systemic inflammation, whilst maintaining a critical role in ongoing immunity protecting against secondary infections. This review aims to summarise the key alterations to myeloid immunity in acute ischaemic stroke, intracerebral haemorrhage (ICH), and subarachnoid haemorrhage (SAH). By integrating clinical and preclinical research, we discover how myeloid immunity is affected across multiple organ systems including the brain, blood, bone marrow, spleen, and lung, and evaluate how these perturbations associate with real-world outcomes including infection. These findings are placed in the context of the rapidly developing field of human immunology, which offers a wealth of opportunity for further research.

Global invasion history and native decline of the common starling: insights through genetics - Katarina C. Stuart; Natalie R. Hofmeister; Julia M. Zichello; Lee A. Rollins (Biological Invasions, 2023)
Few invasive birds are as globally successful as the Common or European Starling ( Sturnus vulgaris ). Native to the Palearctic, the starling has been intentionally introduced to North and South America, South Africa, Australia, and the Pacific Islands, enabling us to explore species traits that may contribute to its invasion success. Coupling the rich studies of life history and more recent explorations of genomic variation among invasions, we illustrate how eco-evolutionary dynamics shape the invasion success of this long-studied and widely distributed species. Especially informative is the comparison between Australian and North American invasions, because these populations colonized novel ranges concurrently and exhibit shared signals of selection despite distinct population histories. In this review, we describe population dynamics across the native and invasive ranges, identify putatively selected traits that may influence the starling’s spread, and suggest possible determinants of starling success world-wide. We also identify future opportunities to utilize this species as a model for avian invasion research, which will inform our understanding of species’ rapid evolution in response to environmental change.

Monitoring and modeling dispersal of a submerged nearshore berm at the mouth of the Columbia River, USA - Andrew W. Stevens; Hans R. Moritz; Edwin P.L. Elias; Guy R. Gelfenbaum; Peter R. Ruggiero; Stuart G. Pearson; James M. McMillan; George M. Kaminsky (Coastal Engineering, 2023)

The hidden cost of road maintenance due to the increased weight of battery and hydrogen trucks and buses—a perspective - John M. Low; R. Stuart Haszeldine; Gareth P. Harrison (Clean Technologies and Environmental Policy, 2023)
Decarbonisation of transport emissions is essential to meet climate targets. For road transport, currently available technologies are battery electric vehicles and hydrogen fuel cell electric vehicles. Battery vehicles are more established than hydrogen; both could deliver the emissions reduction required. However, battery vehicles are considerably heavier than equivalent hydrogen vehicles, which are in turn slightly heavier than internal combustion engine (ICE) vehicles; a heavier vehicle will have a bigger impact on road wear and associated costs. Here we carry out a desk-based analysis, developed in 2021–2022, examining the impact and cost of the increased weight of zero emissions vehicles on road wear in an entire national vehicle fleet. The novelty is in the first quantified application of the long-understood relationship between axle load and road wear to the problem of the additional weight of zero emissions vehicles. This leads to an approximate quantification of additional costs of road maintenance as the vehicle fleet transitions to zero emissions vehicles. We examine these in four scenarios: all battery vehicles; all hydrogen vehicles; a combination; current ICE vehicles for comparison. We find 20–40% additional road wear associated with battery vehicles compared to ICE vehicles; hydrogen leads to a 6% increase. This is overwhelmingly caused by large vehicles – buses, heavy goods vehicles. Smaller vehicles make a negligible contribution. Governmental bodies liable for road maintenance may wish to set weight limits on roads, require additional axles on heavier vehicles, or construct new roads to a higher standard, to decrease road wear. Graphical abstract

Complex crop rotations improve organic nitrogen cycling - Lauren C. Breza; Maria Mooshammer; Timothy M. Bowles; Virginia L. Jin; Marty R. Schmer; Bennett Thompson; A. Stuart Grandy (Soil Biology and Biochemistry, 2023)

Time-varying effects of local weather on behavior and probability of breeding deferral in two Arctic-nesting goose populations - Stephanie A. Cunningham; Toryn L. J. Schafer; Christopher K. Wikle; Jay A. VonBank; Bart M. Ballard; Lei Cao; Stuart Bearhop; Anthony D. Fox; Geoff M. Hilton; Alyn J. Walsh; Larry R. Griffin; Mitch D. Weegman (Oecologia, 2023)
Arctic-nesting geese face energetic challenges during spring migration, including ecological barriers and weather conditions (e.g., precipitation and temperature), which in long-lived species can lead to a trade-off to defer reproduction in favor of greater survival. We used GPS location and acceleration data collected from 35 greater white-fronted geese of the North American midcontinent and Greenland populations at spring migration stopovers, and novel applications of Bayesian dynamic linear models to test daily effects of minimum temperature and precipitation on energy expenditure (i.e., overall dynamic body acceleration, ODBA) and proportion of time spent feeding (PTF), then examined the daily and additive importance of ODBA and PTF on probability of breeding deferral using stochastic antecedent models. We expected distinct responses in behavior and probability of breeding deferral between and within populations due to differences in stopover area availability. Time-varying coefficients of weather conditions were variable between ODBA and PTF, and often did not show consistent patterns among birds, indicating plasticity in how individuals respond to conditions. An increase in antecedent ODBA was associated with a slightly increased probability of deferral in midcontinent geese but not Greenland geese. Probability of deferral decreased with increased PTF in both populations. We did not detect any differentially important time periods. These results suggest either that movements and behavior throughout spring migration do not explain breeding deferral or that ecological linkages between bird decisions during spring and subsequent breeding deferral were different between populations and across migration but occurred at different time scales than those we examined.

Connectivity between countries established by landbirds and raptors migrating along the African–Eurasian flyway - João L. Guilherme; Victoria R. Jones; Inês Catry; Martin Beal; Maria P. Dias; Steffen Oppel; Juliet A. Vickery; Chris M. Hewson; Stuart H. M. Butchart; Ana S. L. Rodrigues (Conservation Biology, 2023)
The conservation of long‐distance migratory birds requires coordination between the multiple countries connected by the movements of these species. The recent expansion of tracking studies is shedding new light on these movements, but much of this information is fragmented and inaccessible to conservation practitioners and policy makers. We synthesized current knowledge on the connectivity established between countries by landbirds and raptors migrating along the African–Eurasian flyway. We reviewed tracking studies to compile migration records for 1229 individual birds, from which we derived 544 migratory links, each link corresponding to a species’ connection between a breeding country in Europe and a nonbreeding country in sub‐Saharan Africa. We used these migratory links to analyze trends in knowledge over time and spatial patterns of connectivity per country (across species), per species (across countries), and at the flyway scale (across all countries and all species). The number of tracking studies available increased steadily since 2010 (particularly for landbirds), but the coverage of existing tracking data was highly incomplete. An average of 7.5% of migratory landbird species and 14.6% of raptor species were tracked per country. More data existed from central and western European countries, and it was biased toward larger bodied species. We provide species‐ and country‐level syntheses of the migratory links we identified from the reviewed studies, involving 123 populations of 43 species, migrating between 28 European and 43 African countries. Several countries (e.g., Spain, Poland, Ethiopia, Democratic Republic of Congo) are strategic priorities for future tracking studies to complement existing data, particularly on landbirds. Despite the limitations in existing tracking data, our data and results can inform discussions under 2 key policy instruments at the flyway scale: the African–Eurasian Migratory Landbirds Action Plan and the Memorandum of Understanding on the Conservation of Migratory Birds of Prey in Africa and Eurasia.

Agriculture without paraquat is feasible without loss of productivity—lessons learned from phasing out a highly hazardous herbicide - Alexander M. Stuart; Charles N. Merfield; Finbarr G. Horgan; Sheila Willis; Meriel A. Watts; Fernando Ramírez-Muñoz; Jorge Sánchez U; Leah Utyasheva; Michael Eddleston; Mark L. Davis; Lars Neumeister; Manoé R. Sanou; et al. (Environmental Science and Pollution Research, 2023)
A small proportion of the thousands of pesticides on the market today are associated with a disproportionately high incidence of severe acute pesticide poisoning and suicide. Paraquat stands out as one of the most lethal pesticides in common use, frequently involved in fatal incidents due to suicides or accidental exposure. Even though paraquat has been banned in over 67 countries, it is still widely used in many others, particularly in Asia and Latin America. Based on a literature review and consultations, this paper identifies options for replacing paraquat and distils practical lessons from numerous successes around the world. Our aim is to support regulators, policymakers, agronomists and the supply chain sector with practical information related to phasing out paraquat . Production data consistently failed to show any negative effects of banning paraquat on agricultural productivity. A wide range of alternative approaches to weed management and crop defoliation are available, many of which do not rely on herbicides. Over 1.25 million farmers in low- and middle-income countries (LMICs) successfully produce a range of crops for private voluntary standards (PVS) in food and fiber supply chains which prohibit paraquat use. We conclude from the findings of this study that eliminating paraquat will save lives without reducing agricultural productivity. Less hazardous and more sustainable alternatives exist. To enhance successful adoption and uptake of these methods on a wide scale, farmers require training and support within an enabling policy environment.

Prediction of enteric methane emissions by sheep using an intercontinental database - Alejandro Belanche; Alexander N. Hristov; Henk J. van Lingen; Stuart E. Denman; Ermias Kebreab; Angela Schwarm; Michael Kreuzer; Mutian Niu; Maguy Eugène; Vincent Niderkorn; Cécile Martin; Harry Archimède; et al. (Journal of Cleaner Production, 2023)

Refuelling infrastructure requirements for renewable hydrogen road fuel through the energy transition - John M. Low; R. Stuart Haszeldine; Julien Mouli-Castillo (Energy Policy, 2023)

Porosity, strength, and alteration – Towards a new volcano stability assessment tool using VNIR-SWIR reflectance spectroscopy - Gabor Kereszturi; Michael Heap; Lauren N. Schaefer; Herlan Darmawan; Frances M. Deegan; Ben Kennedy; Jean-Christophe Komorowski; Stuart Mead; Marina Rosas-Carbajal; Amy Ryan; Valentin R. Troll; Marlène Villeneuve; et al. (Earth and Planetary Science Letters, 2023)

Funding evidence‐based conservation - Danni Parks; Nida Al‐Fulaij; Clare Brook; Stuart H. M. Butchart; Jean‐Gaël Collomb; David Cope; Simon Dowell; Becky Falkingham; Winifred F. Frick; Douglas Gibbs; Emily E. Gray; Nicolas Heard; et al. (Conservation Biology, 2022)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

How to prioritize species recovery after a megafire - Michelle Ward; Josie Carwardine; James E. M. Watson; Anna Pintor; Stephanie Stuart; Hugh P. Possingham; Jonathan R. Rhodes; Alexander R. Carey; Nancy Auerbach; April Reside; Chuan Ji Yong; Ayesha I. T. Tulloch (Conservation Biology, 2022)
Due to climate change, megafires are increasingly common and have sudden, extensive impacts on many species over vast areas, leaving decision makers uncertain about how best to prioritize recovery. We devised a decision‐support framework to prioritize conservation actions to improve species outcomes immediately after a megafire. Complementary locations are selected to extend recovery actions across all fire‐affected species’ habitats. We applied our method to areas burned in the 2019−2020 Australian megafires and assessed its conservation advantages by comparing our results with outcomes of a site‐richness approach (i.e., identifying areas that cost‐effectively recover the most species in any one location). We found that 290 threatened species were likely severely affected and will require immediate conservation action to prevent population declines and possible extirpation. We identified 179 subregions, mostly in southeastern Australia, that are key locations to extend actions that benefit multiple species. Cost savings were over AU$300 million to reduce 95% of threats across all species. Our complementarity‐based prioritization also spread postfire management actions across a wider proportion of the study area compared with the site‐richness method (43% vs. 37% of the landscape managed, respectively) and put more of each species’ range under management (average 90% vs. 79% of every species’ habitat managed). In addition to wildfire response, our framework can be used to prioritize conservation actions that will best mitigate threats affecting species following other extreme environmental events (e.g., floods and drought).

Neurostructural and Neurophysiological Correlates of Multiple Sclerosis Physical Fatigue: Systematic Review and Meta-Analysis of Cross-Sectional Studies - Paula M. Ellison; Stuart Goodall; Niamh Kennedy; Helen Dawes; Allan Clark; Valerie Pomeroy; Martin Duddy; Mark R. Baker; John M. Saxton (Neuropsychology Review, 2022)
Fatigue is one of the most debilitating symptoms for people with multiple sclerosis (PwMS). By consolidating a diverse and conflicting evidence-base, this systematic review and meta-analysis aimed to gain new insights into the neurobiology of MS fatigue. MEDLINE, ProQuest, CINAHL, Web of Science databases and grey literature were searched using Medical Subject Headings. Eligible studies compared neuroimaging and neurophysiological data between people experiencing high (MS-HF) versus low (MS-LF) levels of perceived MS fatigue, as defined by validated fatigue questionnaire cut-points. Data were available from 66 studies, with 46 used for meta-analyses. Neuroimaging studies revealed lower volumetric measures in MS-HF versus MS-LF for whole brain (22.74 ml; 95% CI: -37.72 to -7.76 ml; p = 0.003), grey matter (18.81 ml; 95% CI: 29.60 to 8.03 ml; p < 0.001), putamen (0.40 ml; 95% CI: 0.69 to 0.10 ml; p = 0.008) and acumbens (0.09 ml; 95% CI: 0.15 to 0.03 ml; p = 0.003) and a higher volume of T1-weighted hypointense lesions (1.10 ml; 95% CI: 0.47 to 1.73 ml; p < 0.001). Neurophysiological data showed reduced lower-limb maximum voluntary force production (19.23 N; 95% CI: 35.93 to 2.53 N; p = 0.02) and an attenuation of upper-limb (5.77%; 95% CI:8.61 to 2.93%; p < 0.0001) and lower-limb (2.16%; 95% CI:4.24 to 0.07%; p = 0.04) skeletal muscle voluntary activation, accompanied by more pronounced upper-limb fatigability (5.61%; 95% CI: -9.57 to -1.65%; p = 0.006) in MS-HF versus MS-LF. Results suggest that MS fatigue is characterised by greater cortico-subcortical grey matter atrophy and neural lesions, accompanied by neurophysiological decrements, which include reduced strength and voluntary activation. Prospero registration Prospero registration number: CRD42016017934

Earth stewardship: Shaping a sustainable future through interacting policy and norm shifts - F. Stuart Chapin; Elke U. Weber; Elena M. Bennett; Reinette Biggs; Jeroen van den Bergh; W. Neil Adger; Anne-Sophie Crépin; Stephen Polasky; Carl Folke; Marten Scheffer; Kathleen Segerson; John M. Anderies; et al. (Ambio, 2022)
Transformation toward a sustainable future requires an earth stewardship approach to shift society from its current goal of increasing material wealth to a vision of sustaining built, natural, human, and social capital—equitably distributed across society, within and among nations. Widespread concern about earth’s current trajectory and support for actions that would foster more sustainable pathways suggests potential social tipping points in public demand for an earth stewardship vision. Here, we draw on empirical studies and theory to show that movement toward a stewardship vision can be facilitated by changes in either policy incentives or social norms. Our novel contribution is to point out that both norms and incentives must change and can do so interactively. This can be facilitated through leverage points and complementarities across policy areas, based on values, system design, and agency. Potential catalysts include novel democratic institutions and engagement of non-governmental actors, such as businesses, civic leaders, and social movements as agents for redistribution of power. Because no single intervention will transform the world, a key challenge is to align actions to be synergistic, persistent, and scalable.

Spatial compositional turnover varies with trophic level and body size in marine assemblages of micro‐ and macroorganisms - Amanda K. Pettersen; Melinda A. Coleman; Guillaume Latombe; Sebastian Vadillo Gonzalez; Nathan L. R. Williams; Justin R. Seymour; Alexandra H. Campbell; Torsten Thomas; Renata Ferrari; Rick D. Stuart‐Smith; Graham J. Edgar; Peter D. Steinberg; et al. (Global Ecology and Biogeography, 2022)
Aim Spatial compositional turnover varies considerably among co‐occurring assemblages of organisms, presumably shaped by common processes related to species traits. We investigated patterns of spatial turnover in a diverse set of marine assemblages using zeta diversity, which extends traditional pairwise measures of turnover to capture the roles of both rare and common species in shaping assemblage turnover. We tested the generality of hypothesized patterns related to ecological traits and provide insights into mechanisms of biodiversity change. Location Temperate pelagic and benthic marine assemblages of micro‐ and macroorganisms along south‐eastern Australia (30–36° S latitude). Time period 2008–2021. Major taxa studied Bacteria, phytoplankton, zooplankton, fish, and macrobenthic groups. Methods Six marine datasets spanning bacteria to fishes were collated for measures of “species” occurrence, with a 1° latitude grain. For each assemblage, ecological traits of body size, habitat and trophic level were analysed for the form and rate of decline in zeta diversity and for the species retention rate. Results Species at higher trophic levels showed two to three times the rate of zeta diversity decline compared with lower trophic levels, indicating an increase in turnover from phytoplankton to carnivorous fishes. Body size showed the hypothesized unimodal relationship with rates of turnover for macroorganisms. Patterns of bacterial turnover contrasted with those found for macroorganisms, with the highest levels of turnover in pelagic habitats compared with benthic (kelp‐associated) habitats. The shape of retention rate curves showed the importance of both rare and common species in driving turnover; a finding that would not have been observable using pairwise (beta diversity) measures of turnover. Main conclusions Our results support theoretical predictions for phytoplankton and macroorganisms, showing an increase in turnover rate with trophic level, but these predictions did not hold for bacteria. Such deviations from theory need to be investigated further to identify underlying processes that govern microbial assemblage dynamics.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Data Quality Influences the Predicted Distribution and Habitat of Four Southern-Hemisphere Albatross Species - Kimberly T. Goetz; Fabrice Stephenson; Andrew Hoskins; Aidan D. Bindoff; Rachael A. Orben; Paul M. Sagar; Leigh G. Torres; Caitlin E. Kroeger; Lisa A. Sztukowski; Richard A. Phillips; Stephen C. Votier; Stuart Bearhop; et al. (Frontiers in Marine Science, 2022)
Few studies have assessed the influence of data quality on the predicted probability of occurrence and preferred habitat of marine predators. We compared results from four species distribution models (SDMs) for four southern-hemisphere albatross species, Buller’s ( Thalassarche bulleri ), Campbell ( T. impavida ), grey-headed ( T. chrysostoma ), and white-capped ( T. steadi ), based on datasets of differing quality, ranging from no location data to twice-daily locations of individual birds collected by geolocation devices. Two relative environmental suitability (RES) models were fit using minimum and maximum preferred and absolute values for each environmental variable based on (1) monthly 50% kernel density contours and background environmental data, and (2) primary literature or expert opinion. Additionally, two boosted regression tree (BRT) models were fit using (1) opportunistic sightings data, and (2) geolocation data from bird-borne electronic tags. Using model-specific threshold values, habitat was quantified for each species and model. Model variables included distance from land, bathymetry, sea surface temperature, and chlorophyll- a concentration. Results from both RES models and the BRT model fit with opportunistic sightings were compared to those from the BRT model fit using geolocation data to assess the influence of data quality on predicted occupancy and habitat. For all species, BRT models outperformed RES models. BRT models offer a predictive advantage over RES models by being able to identify relevant variables, incorporate environmental interactions, and provide spatially explicit estimates of model uncertainty. RES models resulted in larger, less refined areas of predicted habitat for all species. Our study highlights the importance of data quality in predicting the distribution and habitat of albatrosses and emphasises the need to consider the pros and cons associated with different levels of data quality when using SDMs to inform management decisions. Furthermore, we examine the overlap in preferred habitat predicted by each SDM with fishing effort. We discuss the influence of data quality on predicting the wide-scale distributions of pelagic seabirds and how these impacts could result in different protection measures.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Differentiating between viruses and virus species by writing their names correctly - Francisco Murilo Zerbini; Stuart G. Siddell; Arcady R. Mushegian; Peter J. Walker; Elliot J. Lefkowitz; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Bas E. Dutilh; María Laura García; Sandra Junglen; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2022)

The use of environmental DNA metabarcoding and quantitative PCR for molecular detection of marine invasive non-native species associated with artificial structures - Laura M. Gargan; Paul R. Brooks; Siobhan R. Vye; Joseph E. Ironside; Stuart R. Jenkins; Tasman P. Crowe; Jens Carlsson (Biological Invasions, 2022)

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Setting priorities for climate change adaptation of Critical Sites in the Africa‐Eurasian waterbird flyways - Frank T. Breiner; Mira Anand; Stuart H. M. Butchart; Martina Flörke; Etienne Fluet‐Chouinard; Antoine Guisan; Lammert Hilarides; Victoria R. Jones; Mikhail Kalyakin; Bernhard Lehner; Merijn van Leeuwen; James W. Pearce‐Higgins; et al. (Global Change Biology, 2022)
Despite their importance for biodiversity and ecosystem services, wetlands are among the most threatened ecosystems globally. The conservation of many migratory waterbirds depends on the conservation of a network of key sites along their flyways. However, the suitability of these sites is changing under climate change, and it is important that management of individual sites in the network adapts to these changes. Using bioclimatic models that also account for changes in inundation, we found that projected climate change will reduce habitat suitability for waterbirds at 57.5% of existing Critical Sites within Africa‐Eurasia, varying from 20.1% in Eastern Europe to 87.0% in Africa. African and Middle East sites are particularly threatened, comprising 71 of the 100 most vulnerable sites. By highlighting priority sites for conservation and classifying Critical Sites into Climate Change Adaptation Strategy (CCAS) classes, our results can be used to support the climate change adaptation of both individual sites and the entire site network.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Functional traits reveal the dominant drivers of long‐term community change across a North American Great Lake - James S. Sinclair; Michael E. Fraker; James M. Hood; Kenneth T. Frank; Mark R. DuFour; Ann Marie Gorman; Stuart A. Ludsin (Global Change Biology, 2021)
Ecosystems worldwide have been impacted by multiple anthropogenic stressors, yet efforts to understand and manage these impacts have been hindered by difficulties in disentangling relative stressor effects. Theoretically, the actions of individual stressors can be delineated based on associated changes in functional traits and these relationships should be generalizable across communities comprised of different species. Thus, combining trait perspectives with community composition data could help to identify the relative influence of different stressors. We evaluated the utility of this combined approach by quantifying shifts in fish species and trait composition in Lake Erie during the past 50 years (1969–2018) in relation to human‐driven changes in nutrient inputs, climate warming, and biological invasions. Species and trait shifts were also compared between two Lake Erie basins, which differ in their environmental and biological characteristics, to identify trait responses that were generalizable across different ecosystems versus those that were context dependent. Our analyses revealed consistent species changes across basins, and shifts in feeding and thermal traits, that were primarily associated with altered nutrient inputs (oligotrophication followed by eutrophication). We found no or inconsistent trait‐based evidence for the effects of warming and two invasive fishes. Context‐dependent trait responses were also evident; nutrient inputs were related to shifts in species tolerant of turbidity in the shallow, eutrophic western basin, which contrasted to shifts between benthopelagic and benthic species in the deeper central basin. Our results reveal the dominant effects of specific stressors on a large freshwater lake and offer a framework for combining species‐based and trait‐based approaches to delineate the impacts of simultaneous stressors on communities of perturbed natural ecosystems.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Establishing the Foundation for the Global Observing System for Marine Life - Erin V. Satterthwaite; Nicholas J. Bax; Patricia Miloslavich; Lavenia Ratnarajah; Gabrielle Canonico; Daniel Dunn; Samantha E. Simmons; Roxanne J. Carini; Karen Evans; Valerie Allain; Ward Appeltans; Sonia Batten; et al. (Frontiers in Marine Science, 2021)
Maintaining healthy, productive ecosystems in the face of pervasive and accelerating human impacts including climate change requires globally coordinated and sustained observations of marine biodiversity. Global coordination is predicated on an understanding of the scope and capacity of existing monitoring programs, and the extent to which they use standardized, interoperable practices for data management. Global coordination also requires identification of gaps in spatial and ecosystem coverage, and how these gaps correspond to management priorities and information needs. We undertook such an assessment by conducting an audit and gap analysis from global databases and structured surveys of experts. Of 371 survey respondents, 203 active, long-term (>5 years) observing programs systematically sampled marine life. These programs spanned about 7% of the ocean surface area, mostly concentrated in coastal regions of the United States, Canada, Europe, and Australia. Seagrasses, mangroves, hard corals, and macroalgae were sampled in 6% of the entire global coastal zone. Two-thirds of all observing programs offered accessible data, but methods and conditions for access were highly variable. Our assessment indicates that the global observing system is largely uncoordinated which results in a failure to deliver critical information required for informed decision-making such as, status and trends, for the conservation and sustainability of marine ecosystems and provision of ecosystem services. Based on our study, we suggest four key steps that can increase the sustainability, connectivity and spatial coverage of biological Essential Ocean Variables in the global ocean: (1) sustaining existing observing programs and encouraging coordination among these; (2) continuing to strive for data strategies that follow FAIR principles (findable, accessible, interoperable, and reusable); (3) utilizing existing ocean observing platforms and enhancing support to expand observing along coasts of developing countries, in deep ocean basins, and near the poles; and (4) targeting capacity building efforts. Following these suggestions could help create a coordinated marine biodiversity observing system enabling ecological forecasting and better planning for a sustainable use of ocean resources.

Characterization of clinical Ralstonia strains and their taxonomic position - Ad C. Fluit; Jumamurat R. Bayjanov; María Díez Aguilar; Rafael Cantón; Michael M. Tunney; J. Stuart Elborn; Mireille van Westreenen; Miquel B. Ekkelenkamp (Antonie van Leeuwenhoek, 2021)
To improve understanding of the role of Ralstonia in cystic fibrosis (CF), whole genomes of 18 strains from clinical samples were sequenced using Illumina technology. Sequences were analysed by core genome Multi-Locus Sequence Typing, Average Nucleotide Identity based on BLAST (ANIb), RAST annotation, and by ResFinder. Phylogenetic analysis was performed for the 16S rRNA gene, and the OXA-22 and OXA-60 ß-lactamase families. The minimal inhibitory concentrations (MICs) were determined using broth microdilution. ANIb data for the 18 isolates and 54 strains from GenBank, supported by phylogenetic analysis, showed that 8 groups of clusters (A-H), as well as subgroups that should be considered as species or subspecies. Groups A-C contain strains previously identified as Ralstonia solanacearum and Ralstonia pseudosolanacearum . We propose that group A is a novel species. Group B and C are Ralstonia syzygii , Ralstonia solanacearum , respectively. Group D is composed of Ralstonia mannitolilytica and Group E of Ralstonia pickettii . Group F and G should be considered novel species. Group H strains belong to R. insidiosa . OXA-22 and OXA-60 family ß-lactamases were encoded by all strains. Co-trimoxazole generally showed high activity with low MICs (≤1 mg/l) as did ciprofloxacin (≤0.12 mg/l). MICs against the other antibiotics were more variable, but generally high. RAST annotation revealed limited differences between the strains, and virulence factors were not identified. The taxonomy of the genus Ralstonia is in need of revision, but sequencing additional isolates is needed. Antibiotic resistance levels are high. Annotation did not identify potential virulence factors.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

Host Identity as a Driver of Moss-Associated N2 Fixation Rates in Alaska - Julia E. M. Stuart; Hannah Holland-Moritz; Lily R. Lewis; Mélanie Jean; Samantha N. Miller; Stuart F. McDaniel; Noah Fierer; José Miguel Ponciano; Michelle C. Mack (Ecosystems, 2021)

Workflow for the Generation of Expert-Derived Training and Validation Data: A View to Global Scale Habitat Mapping - Chris M. Roelfsema; Mitchell Lyons; Nicholas Murray; Eva M. Kovacs; Emma Kennedy; Kathryn Markey; Rodney Borrego-Acevedo; Alexandra Ordoñez Alvarez; Chantel Say; Paul Tudman; Meredith Roe; Jeremy Wolff; et al. (Frontiers in Marine Science, 2021)
Our ability to completely and repeatedly map natural environments at a global scale have increased significantly over the past decade. These advances are from delivery of a range of on-line global satellite image archives and global-scale processing capabilities, along with improved spatial and temporal resolution satellite imagery. The ability to accurately train and validate these global scale-mapping programs from what we will call “reference data sets” is challenging due to a lack of coordinated financial and personnel resourcing, and standardized methods to collate reference datasets at global spatial extents. Here, we present an expert-driven approach for generating training and validation data on a global scale, with the view to mapping the world’s coral reefs. Global reefs were first stratified into approximate biogeographic regions, then per region reference data sets were compiled that include existing point data or maps at various levels of accuracy. These reference data sets were compiled from new field surveys, literature review of published surveys, and from individually sourced contributions from the coral reef monitoring and management agencies. Reference data were overlaid on high spatial resolution satellite image mosaics (3.7 m × 3.7 m pixels; Planet Dove) for each region. Additionally, thirty to forty satellite image tiles; 20 km × 20 km) were selected for which reference data and/or expert knowledge was available and which covered a representative range of habitats. The satellite image tiles were segmented into interpretable groups of pixels which were manually labeled with a mapping category via expert interpretation. The labeled segments were used to generate points to train the mapping models, and to validate or assess accuracy. The workflow for desktop reference data creation that we present expands and up-scales traditional approaches of expert-driven interpretation for both manual habitat mapping and map training/validation. We apply the reference data creation methods in the context of global coral reef mapping, though our approach is broadly applicable to any environment. Transparent processes for training and validation are critical for usability as big data provide more opportunities for managers and scientists to use global mapping products for science and conservation of vulnerable and rapidly changing ecosystems.

Small invertebrates in bivalve-cultivated and unmodified habitats of nearshore ecosystems - Stuart H. Munsch; Julie S. Barber; Jeffery R. Cordell; Peter M. Kiffney; Beth L. Sanderson; Jason D. Toft (Hydrobiologia, 2021)
Many nearshore ecosystems are modified by aquaculture, including bivalve culture to produce food and restore extirpated populations. Small invertebrates in nearshore ecosystems support fundamental ecological processes, but the effects of bivalve culture on invertebrates are incompletely understood. Here, we compared invertebrate assemblages from multiple studies of bivalve-cultivated and unmodified nearshore habitats along the US west coast. In general, unmodified eelgrass and nearby off-bottom culture habitats with eelgrass present were inhabited by a greater abundance, richness, and diversity of epibenthic invertebrates than bottom culture and bare (mud, sand) habitats that both lacked eelgrass. Findings of individual studies suggested: minor differences in epibenthic invertebrate assemblages associated with various aquaculture practices; restoring native oysters to mudflats did not detectably alter epibenthic invertebrate abundances; epibenthic invertebrates were more abundant on shell hash introduced to mudflats than unmodified mudflats; and benthic invertebrates were less abundant, rich, and diverse in habitats cultured on bottom by Manila clams. Considering the range of these patterns, there appears to be potential for coastal communities to restore extirpated bivalve populations or develop bivalve culture practices that meet objectives to grow food while maintaining nearshore ecosystems’ fundamental processes supported by robust invertebrate assemblages.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

A Multi-Model Pipeline for Translational Intracerebral Haemorrhage Research - Sarah E. Withers; Adrian R. Parry-Jones; Stuart M. Allan; Paul R. Kasher (Translational Stroke Research, 2020)
Apart from acute and chronic blood pressure lowering, we have no specific medications to prevent intracerebral haemorrhage (ICH) or improve outcomes once bleeding has occurred. One reason for this may be related to particular limitations associated with the current pre-clinical models of ICH, leading to a failure to translate into the clinic. It would seem that a breakdown in the ‘drug development pipeline’ currently exists for translational ICH research which needs to be urgently addressed. Here, we review the most commonly used pre-clinical models of ICH and discuss their advantages and disadvantages in the context of translational studies. We propose that to increase our chances of successfully identifying new therapeutics for ICH, a bi-directional, 2- or 3-pronged approach using more than one model species/system could be useful for confirming key pre-clinical observations. Furthermore, we highlight that post-mortem/ex-vivo ICH patient material is a precious and underused resource which could play an essential role in the verification of experimental results prior to consideration for further clinical investigation. Embracing multidisciplinary collaboration between pre-clinical and clinical ICH research groups will be essential to ensure the success of this type of approach in the future.

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

Changes to virus taxonomy and the Statutes ratified by the International Committee on Taxonomy of Viruses (2020) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; et al. (Archives of Virology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Rodent damage to rice crops is not affected by the water-saving technique, alternate wetting and drying - Renee P. Lorica; Grant R. Singleton; Alexander M. Stuart; Steven R. Belmain (Journal of Pest Science, 2020)

Habitat maps to enhance monitoring and management of the Great Barrier Reef - Chris M. Roelfsema; Eva M. Kovacs; Juan Carlos Ortiz; David P. Callaghan; Karlo Hock; Mathieu Mongin; Kasper Johansen; Peter J. Mumby; Magnus Wettle; Mike Ronan; Petra Lundgren; Emma V. Kennedy; et al. (Coral Reefs, 2020)

Tiered analysis of whole-exome sequencing for epilepsy diagnosis - Paul J. Dunn; Bridget H. Maher; Cassie L. Albury; Shani Stuart; Heidi G. Sutherland; Neven Maksemous; Miles C. Benton; Robert A. Smith; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2020)

Correction to: Binomial nomenclature for virus species: a consultation - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2020)
The article Binomial nomenclature for virus species: a consultation, written by Stuart G. Siddell, Peter J. Walker, Elliot J. Lefkowitz, Arcady R. Mushegian, Bas E. Dutilh.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Sexual reproduction in populations of Austropuccinia psidii - Alistair R. McTaggart; Esna du Plessis; Jolanda Roux; Irene Barnes; Stuart Fraser; Ginna M. Granados; Wellcome W. H. Ho; Louise S. Shuey; André Drenth (European Journal of Plant Pathology, 2020)

Binomial nomenclature for virus species: a consultation - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; et al. (Archives of Virology, 2020)
The Executive Committee of the International Committee on Taxonomy of Viruses (ICTV) recognizes the need for a standardized nomenclature for virus species. This article sets out the case for establishing a binomial nomenclature and presents the advantages and disadvantages of different naming formats. The Executive Committee understands that adopting a binomial system would have major practical consequences, and invites comments from the virology community before making any decisions to change the existing nomenclature. The Executive Committee will take account of these comments in deciding whether to approve a standardized binomial system at its next meeting in October 2020. Note that this system would relate only to the formal names of virus species and not to the names of viruses.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Fish Diet Shifts Associated with the Northern Gulf of Mexico Hypoxic Zone - Cassandra N. Glaspie; Melissa Clouse; Klaus Huebert; Stuart A. Ludsin; Doran M. Mason; James J. Pierson; Michael R. Roman; Stephen B. Brandt (Estuaries and Coasts, 2019)

Changes to virus taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2019) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

SMART Cables for Observing the Global Ocean: Science and Implementation - Bruce M. Howe; Brian K. Arbic; Jérome Aucan; Christopher R. Barnes; Nigel Bayliff; Nathan Becker; Rhett Butler; Laurie Doyle; Shane Elipot; Gregory C. Johnson; Felix Landerer; Stephen Lentz; et al. (Frontiers in Marine Science, 2019)

Additional changes to taxonomy ratified in a special vote by the International Committee on Taxonomy of Viruses (October 2018) - Stuart G. Siddell; Peter J. Walker; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; et al. (Archives of Virology, 2019)

Body size, reef area and temperature predict global reef‐fish species richness across spatial scales - D. R. Barneche; E. L. Rezende; V. Parravicini; E. Maire; G. J. Edgar; R. D. Stuart‐Smith; J. E. Arias‐González; C. E. L. Ferreira; A. M. Friedlander; A. L. Green; O. J. Luiz; F. A. Rodríguez‐Zaragoza; et al. (Global Ecology and Biogeography, 2019)
Aim To investigate biotic and abiotic correlates of reef‐fish species richness across multiple spatial scales. Location Tropical reefs around the globe, including 485 sites in 109 sub‐provinces spread across 14 biogeographic provinces. Time period Present. Major taxa studied 2,523 species of reef fish. Methods We compiled a database encompassing 13,050 visual transects. We used hierarchical linear Bayesian models to investigate whether fish body size, reef area, isolation, temperature, and anthropogenic impacts correlate with reef‐fish species richness at each spatial scale (i.e., sites, sub‐provinces, provinces). Richness was estimated using coverage‐based rarefaction. We also tested whether species packing (i.e., transect‐level species richness/m 2 ) is correlated with province‐level richness. Results Body size had the strongest effect on species richness across all three spatial scales. Reef area and temperature were both positively correlated with richness at all spatial scales. At the site scale only, richness decreased with reef isolation. Species richness was not correlated with proxies of human impacts. Species packing was correlated with species richness at the province level following a sub‐linear power function. Province‐level differences in species richness were also mirrored by patterns of body size distribution at the site scale. Species‐rich provinces exhibited heterogeneous assemblages of small‐bodied species with small range sizes, whereas species‐poor provinces encompassed homogeneous assemblages composed by larger species with greater dispersal capacity. Main conclusions Our findings suggest that body size distribution, reef area and temperature are major predictors of species richness and accumulation across scales, consistent with recent theories linking home range to species–area relationships as well as metabolic effects on speciation rates. Based on our results, we hypothesize that in less diverse areas, species are larger and likely more dispersive, leading to larger range sizes and less turnover between sites. Our results indicate that changes in province‐level (i.e., regional) richness should leave a tractable fingerprint in local assemblages, and that detailed studies on local‐scale assemblage composition may be informative of responses occurring at larger scales.

Methylglyoxal-induced enhancement of somatic embryogenesis and associated metabolic changes in sugarcane (Saccharum spp. hybrids) - Tendekai Mahlanza; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Seasonal and Long-Term Dynamics in Stream Water Sodium Chloride Concentrations and the Effectiveness of Road Salt Best Management Practices - Victoria R. Kelly; Stuart E. Findlay; Stephen K. Hamilton; Gary M. Lovett; Kathleen C. Weathers (Water, Air, & Soil Pollution, 2019)

Resistance training in young men induces muscle transcriptome-wide changes associated with muscle structure and metabolism refining the response to exercise-induced stress - Felipe Damas; Carlos Ugrinowitsch; Cleiton A. Libardi; Paulo R. Jannig; Amy J. Hector; Chris McGlory; Manoel E. Lixandrão; Felipe C. Vechin; Horacio Montenegro; Valmor Tricoli; Hamilton Roschel; Stuart M. Phillips (European Journal of Applied Physiology, 2018)

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Presence of a generalist entomopathogenic fungus influences the oviposition behaviour of an aphid-specific predator - A. G. C. de Azevedo; R. M. Stuart; L. Sigsgaard (BioControl, 2018)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2018) - Andrew M. Q. King; Elliot J. Lefkowitz; Arcady R. Mushegian; Michael J. Adams; Bas E. Dutilh; Alexander E. Gorbalenya; Balázs Harrach; Robert L. Harrison; Sandra Junglen; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; et al. (Archives of Virology, 2018)

Agronomic evaluation and molecular characterisation of the acetolactate synthase gene in imazapyr tolerant sugarcane (Saccharum hybrid) genotypes - Motselisi J. Koetle; Dyfed Lloyd Evans; Varnika Singh; Sandy J. Snyman; R. Stuart Rutherford; M. Paula Watt (Plant Cell Reports, 2018)

Effects of long-term dietary administration of estrogen receptor-beta agonist diarylpropionitrile on ovariectomized female ICR (CD-1) mice - Sherry A. Said; Rachel Isedowo; Christilynn Guerin; Navreek N. Nar; Leesa Lillie; Shawn Bukovac; Jonathan J. Simone; Matthew R. Green; Cheryl M. McCormick; Jeffrey A. Stuart (GeroScience, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Towards automation of glycomic profiling of complex biological materials - Archana Shubhakar; Poh-Choo Pang; Daryl L. Fernandes; Anne Dell; Daniel I. R. Spencer; Stuart M. Haslam (Glycoconjugate Journal, 2018)

Impact of multiple stressors on juvenile fish in estuaries of the northeast Pacific - Jason D. Toft; Stuart H. Munsch; Jeffery R. Cordell; Kiira Siitari; Van C. Hare; Brett M. Holycross; Lisa A. DeBruyckere; Correigh M. Greene; Brent B. Hughes (Global Change Biology, 2018)
A key step in identifying global change impacts on species and ecosystems is to quantify effects of multiple stressors. To date, the science of global change has been dominated by regional field studies, experimental manipulation, meta‐analyses, conceptual models, reviews, and studies focusing on a single stressor or species over broad spatial and temporal scales. Here, we provide one of the first studies for coastal systems examining multiple stressor effects across broad scales, focused on the nursery function of 20 estuaries spanning 1,600 km of coastline, 25 years of monitoring, and seven fish and invertebrate species along the northeast Pacific coast. We hypothesized those species most estuarine dependent and negatively impacted by human activities would have lower presence and abundances in estuaries with greater anthropogenic land cover, pollution, and water flow stress. We found significant negative relationships between juveniles of two of seven species (Chinook salmon and English sole) and estuarine stressors. Chinook salmon were less likely to occur and were less abundant in estuaries with greater pollution stress. They were also less abundant in estuaries with greater flow stress, although this relationship was marginally insignificant. English sole were less abundant in estuaries with greater land cover stress. Together, we provide new empirical evidence that effects of stressors on two fish species culminate in detectable trends along the northeast Pacific coast, elevating the need for protection from pollution, land cover, and flow stressors to their habitats. Lack of response among the other five species could be related to differing resistance to specific stressors, type and precision of the stressor metrics, and limitations in catch data across estuaries and habitats. Acquiring improved measurements of impacts to species will guide future management actions, and help predict how estuarine nursery functions can be optimized given anthropogenic stressors and climate change scenarios.

Biophysical drivers of coral trophic depth zonation - Gareth J. Williams; Stuart A. Sandin; Brian J. Zgliczynski; Michael D. Fox; Jamison M. Gove; Justin S. Rogers; Kathryn A. Furby; Aaron C. Hartmann; Zachary R. Caldwell; Nichole N. Price; Jennifer E. Smith (Marine Biology, 2018)

Successional convergence in experimentally disturbed intertidal communities - Gustavo M. Martins; Francisco Arenas; Fernando Tuya; Rubén Ramírez; Ana I. Neto; Stuart R. Jenkins (Oecologia, 2018)

Brain cortical characteristics of lifetime cognitive ageing - Simon R. Cox; Mark E. Bastin; Stuart J. Ritchie; David Alexander Dickie; Dave C. Liewald; Susana Muñoz Maniega; Paul Redmond; Natalie A. Royle; Alison Pattie; Maria Valdés Hernández; Janie Corley; Benjamin S. Aribisala; et al. (Brain Structure and Function, 2018)

Risk and protective factors for structural brain ageing in the eighth decade of life - Stuart J. Ritchie; Elliot M. Tucker-Drob; Simon R. Cox; David Alexander Dickie; Maria del C. Valdés Hernández; Janie Corley; Natalie A. Royle; Paul Redmond; Susana Muñoz Maniega; Alison Pattie; Benjamin S. Aribisala; Adele M. Taylor; et al. (Brain Structure and Function, 2017)

Idiosyncratic responses to climate‐driven forest fragmentation and marine incursions in reed frogs from Central Africa and the Gulf of Guinea Islands - Rayna C. Bell; Juan L. Parra; Gabriel Badjedjea; Michael F. Barej; David C. Blackburn; Marius Burger; Alan Channing; Jonas Maximilian Dehling; Eli Greenbaum; Václav Gvoždík; Jos Kielgast; Chifundera Kusamba; et al. (Molecular Ecology, 2017)
Organismal traits interact with environmental variation to mediate how species respond to shared landscapes. Thus, differences in traits related to dispersal ability or physiological tolerance may result in phylogeographic discordance among co‐distributed taxa, even when they are responding to common barriers. We quantified climatic suitability and stability, and phylogeographic divergence within three reed frog species complexes across the Guineo‐Congolian forests and Gulf of Guinea archipelago of Central Africa to investigate how they responded to a shared climatic and geological history. Our species‐specific estimates of climatic suitability through time are consistent with temporal and spatial heterogeneity in diversification among the species complexes, indicating that differences in ecological breadth may partly explain these idiosyncratic patterns. Likewise, we demonstrated that fluctuating sea levels periodically exposed a land bridge connecting Bioko Island with the mainland Guineo‐Congolian forest and that habitats across the exposed land bridge likely enabled dispersal in some species, but not in others. We did not find evidence that rivers are biogeographic barriers across any of the species complexes. Despite marked differences in the geographic extent of stable climates and temporal estimates of divergence among the species complexes, we recovered a shared pattern of intermittent climatic suitability with recent population connectivity and demographic expansion across the Congo Basin. This pattern supports the hypothesis that genetic exchange across the Congo Basin during humid periods, followed by vicariance during arid periods, has shaped regional diversity. Finally, we identified many distinct lineages among our focal taxa, some of which may reflect incipient or unrecognized species.

Is Climate Change Shifting the Poleward Limit of Mangroves? - Sharyn M. Hickey; Stuart R. Phinn; Nik J. Callow; Kimberly P. Van Niel; Jeff E. Hansen; Carlos M. Duarte (Estuaries and Coasts, 2017)

Ion channelopathies and migraine pathogenesis - Cassie L. Albury; Shani Stuart; Larisa M. Haupt; Lyn R. Griffiths (Molecular Genetics and Genomics, 2017)

Changes to taxonomy and the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2017) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max L. Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

Integrated approach to determining stock structure: implications for fisheries management of sardine, Sardinops sagax, in Australian waters - Christopher Izzo; Tim M. Ward; Alex R. Ivey; Iain M. Suthers; John Stewart; Stuart C. Sexton; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2017)

A global analysis of traits predicting species sensitivity to habitat fragmentation - Douglas A. Keinath; Daniel F. Doak; Karen E. Hodges; Laura R. Prugh; William Fagan; Cagan H. Sekercioglu; Stuart H. M. Buchart; Matthew Kauffman (Global Ecology and Biogeography, 2017)
Aim Elucidating patterns in species responses to habitat fragmentation is an important focus of ecology and conservation, but studies are often geographically restricted, taxonomically narrow or use indirect measures of species vulnerability. We investigated predictors of species presence after fragmentation using data from studies around the world that included all four terrestrial vertebrate classes, thus allowing direct inter‐taxonomic comparison. Location World‐wide. Methods We used generalized linear mixed‐effect models in an information theoretic framework to assess the factors that explained species presence in remnant habitat patches (3342 patches; 1559 species, mostly birds; and 65,695 records of patch‐specific presence–absence). We developed a novel metric of fragmentation sensitivity, defined as the maximum rate of change in probability of presence with changing patch size (‘Peak Change’), to distinguish between general rarity on the landscape and sensitivity to fragmentation per se. Results Size of remnant habitat patches was the most important driver of species presence. Across all classes, habitat specialists, carnivores and larger species had a lower probability of presence, and those effects were substantially modified by interactions. Sensitivity to fragmentation (measured by Peak Change) was influenced primarily by habitat type and specialization, but also by fecundity, life span and body mass. Reptiles were more sensitive than other classes. Grassland species had a lower probability of presence, though sample size was relatively small, but forest and shrubland species were more sensitive. Main conclusions Habitat relationships were more important than life‐history characteristics in predicting the effects of fragmentation. Habitat specialization increased sensitivity to fragmentation and interacted with class and habitat type; forest specialists and habitat‐specific reptiles were particularly sensitive to fragmentation. Our results suggest that when conservationists are faced with disturbances that could fragment habitat they should pay particular attention to specialists, particularly reptiles. Further, our results highlight that the probability of presence in fragmented landscapes and true sensitivity to fragmentation are predicted by different factors.

Provenance does matter: links between winter trophic segregation and the migratory origins of European robins - Paulo Catry; Ana R. Campos; José Pedro Granadeiro; Júlio M. Neto; Jaime Ramos; Jason Newton; Stuart Bearhop (Oecologia, 2016)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2016) - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Brain white matter structure and information processing speed in healthy older age - Ksenia A. Kuznetsova; Susana Muñoz Maniega; Stuart J. Ritchie; Simon R. Cox; Amos J. Storkey; John M. Starr; Joanna M. Wardlaw; Ian J. Deary; Mark E. Bastin (Brain Structure and Function, 2016)

Incorporating benthic community changes into hydrochemical-based projections of coral reef calcium carbonate production under ocean acidification - Emily C. Shaw; Sarah M. Hamylton; Stuart R. Phinn (Coral Reefs, 2016)

Glycoproteomic studies of IgE from a novel hyper IgE syndrome linked to PGM3 mutation - Gang Wu; Paul G. Hitchen; Maria Panico; Simon J. North; Mohamed-Ridha Barbouche; Daniel Binet; Howard R. Morris; Anne Dell; Stuart M. Haslam (Glycoconjugate Journal, 2016)

Phylogeography of the harvestman genus Metasiro (Arthropoda, Arachnida, Opiliones) reveals a potential solution to the Pangean paradox - Ronald M. Clouse; Prashant P. Sharma; Jessie C. Stuart; Lloyd R. Davis; Gonzalo Giribet; Sarah L. Boyer; Ward C. Wheeler (Organisms Diversity & Evolution, 2016)

Tectonic subsidence provides insight into possible coral reef futures under rapid sea-level rise - Megan I. Saunders; Simon Albert; Chris M. Roelfsema; Javier X. Leon; Colin D. Woodroffe; Stuart R. Phinn; Peter J. Mumby (Coral Reefs, 2016)

Migratory diversity predicts population declines in birds - James J. Gilroy; Jennifer A. Gill; Stuart H. M. Butchart; Victoria R. Jones; Aldina M. A. Franco (Ecology Letters, 2016)
Declines in migratory species are a pressing concern worldwide, but the mechanisms underpinning these declines are not fully understood. We hypothesised that species with greater within‐population variability in migratory movements and destinations, here termed ‘migratory diversity’, might be more resilient to environmental change. To test this, we related map‐based metrics of migratory diversity to recent population trends for 340 European breeding birds. Species that occupy larger non‐breeding ranges relative to breeding, a characteristic we term ‘migratory dispersion’, were less likely to be declining than those with more restricted non‐breeding ranges. Species with partial migration strategies (i.e. overlapping breeding and non‐breeding ranges) were also less likely to be declining than full migrants or full residents, an effect that was independent of migration distance. Recent rates of advancement in Europe‐wide spring arrival date were greater for partial migrants than full migrants, suggesting that migratory diversity may also help facilitate species responses to climate change.

Genotypic variation in foundation species generates network structure that may drive community dynamics and evolution - Matthew K. Lau; Arthur R. Keith; Stuart R. Borrett; Stephen M. Shuster; Thomas G. Whitham (Ecology, 2016)
Although genetics in a single species is known to impact whole communities, little is known about how genetic variation influences species interaction networks in complex ecosystems. Here, we examine the interactions in a community of arthropod species on replicated genotypes (clones) of a foundation tree species, Populus angustifolia James (narrowleaf cottonwood), in a long‐term, common garden experiment using a bipartite “genotype–species” network perspective. We combine this empirical work with a simulation experiment designed to further investigate how variation among individual tree genotypes can impact network structure. Three findings emerged: (1) the empirical “genotype–species network” exhibited significant network structure with modularity being greater than the highly conservative null model; (2) as would be expected given a modular network structure, the empirical network displayed significant positive arthropod co‐occurrence patterns; and (3) furthermore, the simulations of “genotype–species” networks displayed variation in network structure, with modularity in particular clearly increasing, as genotypic variation increased. These results support the conclusion that genetic variation in a single species contributes to the structure of ecological interaction networks, which could influence ecological dynamics (e.g., assembly and stability) and evolution in a community context.

Low rates of endocarditis in healthcare-associated Staphylococcus aureus bacteremia suggest that echocardiography might not always be required - T. Barton; S. Moir; H. Rehmani; I. Woolley; T. M. Korman; R. L. Stuart (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Thalamocortical neurons display suppressed burst-firing due to an enhanced Ih current in a genetic model of absence epilepsy - Stuart M. Cain; John R. Tyson; Karen L. Jones; Terrance P. Snutch (Pflügers Archiv - European Journal of Physiology, 2015)

Potential of Fusarium sacchari-tolerant mutants in controlling Eldana saccharina and borer-associated Fusarium stem rot in sugarcane - Tendekai Mahlanza; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (European Journal of Plant Pathology, 2015)

Estimating the normal background rate of species extinction - Jurriaan M. De Vos; Lucas N. Joppa; John L. Gittleman; Patrick R. Stephens; Stuart L. Pimm (Conservation Biology, 2015)
A key measure of humanity's global impact is by how much it has increased species extinction rates. Familiar statements are that these are 100–1000 times pre‐human or background extinction levels. Estimating recent rates is straightforward, but establishing a background rate for comparison is not. Previous researchers chose an approximate benchmark of 1 extinction per million species per year (E/MSY). We explored disparate lines of evidence that suggest a substantially lower estimate. Fossil data yield direct estimates of extinction rates, but they are temporally coarse, mostly limited to marine hard‐bodied taxa, and generally involve genera not species. Based on these data, typical background loss is 0.01 genera per million genera per year. Molecular phylogenies are available for more taxa and ecosystems, but it is debated whether they can be used to estimate separately speciation and extinction rates. We selected data to address known concerns and used them to determine median extinction estimates from statistical distributions of probable values for terrestrial plants and animals. We then created simulations to explore effects of violating model assumptions. Finally, we compiled estimates of diversification—the difference between speciation and extinction rates for different taxa. Median estimates of extinction rates ranged from 0.023 to 0.135 E/MSY. Simulation results suggested over‐ and under‐estimation of extinction from individual phylogenies partially canceled each other out when large sets of phylogenies were analyzed. There was no evidence for recent and widespread pre‐human overall declines in diversity. This implies that average extinction rates are less than average diversification rates. Median diversification rates were 0.05–0.2 new species per million species per year. On the basis of these results, we concluded that typical rates of background extinction may be closer to 0.1 E/MSY. Thus, current extinction rates are 1,000 times higher than natural background rates of extinction and future rates are likely to be 10,000 times higher. Estimación de la Tasa Normal de Extinción de Especies

Exploiting fungal cell wall components in vaccines - Stuart M. Levitz; Haibin Huang; Gary R. Ostroff; Charles A. Specht (Seminars in Immunopathology, 2015)

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Prioritizing islands for the eradication of invasive vertebrates in the United Kingdom overseas territories - Jeffrey Dawson; Steffen Oppel; Richard J. Cuthbert; Nick Holmes; Jeremy P. Bird; Stuart H. M. Butchart; Dena R. Spatz; Bernie Tershy (Conservation Biology, 2015)
Invasive alien species are one of the primary threats to native biodiversity on islands worldwide. Consequently, eradicating invasive species from islands has become a mainstream conservation practice. Deciding which islands have the highest priority for eradication is of strategic importance to allocate limited resources to achieve maximum conservation benefit. Previous island prioritizations focused either on a narrow set of native species or on a small geographic area. We devised a prioritization approach that incorporates all threatened native terrestrial vertebrates and all invasive terrestrial vertebrates occurring on 11 U.K. overseas territories, which comprise over 2000 islands ranging from the sub‐Antarctic to the tropics. Our approach includes eradication feasibility and distinguishes between the potential and realistic conservation value of an eradication, which reflects the benefit that would accrue following eradication of either all invasive species or only those species for which eradication techniques currently exist. We identified the top 25 priority islands for invasive species eradication that together would benefit extant populations of 155 native species including 45 globally threatened species. The 5 most valuable islands included the 2 World Heritage islands Gough (South Atlantic) and Henderson (South Pacific) that feature unique seabird colonies, and Anegada, Little Cayman, and Guana Island in the Caribbean that feature a unique reptile fauna. This prioritization can be rapidly repeated if new information or techniques become available, and the approach could be replicated elsewhere in the world. Priorización de Islas para la Erradicación de Vertebrados Invasores en los Territorios Exteriores del Reino Unido

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Experimental evidence that invasive grasses use allelopathic biochemicals as a potential mechanism for invasion: chemical warfare in nature - Mitchell J. Greer; Gail W. T. Wilson; Karen R. Hickman; Stuart M. Wilson (Plant and Soil, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

The Biogeography of Globally Threatened Seabirds and Island Conservation Opportunities - DENA R. SPATZ; KELLY M. NEWTON; REINA HEINZ; BERNIE TERSHY; NICK D. HOLMES; STUART H. M. BUTCHART; DONALD A. CROLL (Conservation Biology, 2014)
Seabirds are the most threatened group of marine animals; 29% of species are at some risk of extinction. Significant threats to seabirds occur on islands where they breed, but in many cases, effective island conservation can mitigate these threats. To guide island‐based seabird conservation actions, we identified all islands with extant or extirpated populations of the 98 globally threatened seabird species, as recognized on the International Union for Conservation of Nature Red List, and quantified the presence of threatening invasive species, protected areas, and human populations. We matched these results with island attributes to highlight feasible island conservation opportunities. We identified 1362 threatened breeding seabird populations on 968 islands. On 803 (83%) of these islands, we identified threatening invasive species (20%), incomplete protected area coverage (23%), or both (40%). Most islands with threatened seabirds are amenable to island‐wide conservation action because they are small (57% were 2 ), uninhabited (74%), and occur in high‐ or middle‐income countries (96%). Collectively these attributes make islands with threatened seabirds a rare opportunity for effective conservation at scale. La Biogeografía de Aves Marinas Amenazadas Globalmente y las Oportunidades de Conservación en Islas

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Life history traits of Blaptostethus pallescens (Hemiptera: Anthocoridae), a candidate for use in augmentative biological control in Egypt - Islam S. Sobhy; Amany M. Abdul-Hamid; Awad A. Sarhan; Ahmed A. Shoukry; Nasser S. Mandour; Stuart R. Reitz (Applied Entomology and Zoology, 2014)

Multiple environmental controls on phytoplankton growth strategies determine adaptive responses of the N : P ratio - Stuart J. Daines; James R. Clark; Timothy M. Lenton (Ecology Letters, 2014)
The controls on the ‘Redfield’ N : P stoichiometry of marine phytoplankton and hence the N : P ratio of the deep ocean remain incompletely understood. Here, we use a model for phytoplankton ecophysiology and growth, based on functional traits and resource‐allocation trade‐offs, to show how environmental filtering, biotic interactions, and element cycling in a global ecosystem model determine phytoplankton biogeography, growth strategies and macromolecular composition. Emergent growth strategies capture major observed patterns in marine biomes. Using a new synthesis of experimental RNA and protein measurements to constrain per‐ribosome translation rates, we determine a spatially variable lower limit on adaptive rRNA:protein allocation and hence on the relationship between the largest cellular P and N pools. Comparison with the lowest observed phytoplankton N : P ratios and N : P export fluxes in the Southern Ocean suggests that additional contributions from phospholipid and phosphorus storage compounds play a fundamental role in determining the marine biogeochemical cycling of these elements.

Mesozoic exhumation history and palaeolandscape of the Iberian Massif in eastern Galicia from apatite fission-track and (U+Th)/He data - R. W. Grobe; J. Alvarez-Marrón; U. A. Glasmacher; F. M. Stuart (International Journal of Earth Sciences, 2014)

Gradient compression garments protect against orthostatic intolerance during recovery from bed rest - Michael B. Stenger; Stuart M. C. Lee; L. Christine Ribeiro; Tiffany R. Phillips; Robert J. Ploutz-Snyder; Michael C. Willig; Christian M. Westby; Steven H. Platts (European Journal of Applied Physiology, 2014)

Differences between Han Chinese and Caucasians in transcranial magnetic stimulation parameters - Xiang Yi; Karen M. Fisher; Ming Lai; Kashif Mansoor; R. Bicker; Stuart N. Baker (Experimental Brain Research, 2014)

Periprosthetic osteolysis after total hip replacement: molecular pathology and clinical management - Donald W. Howie; Susan D. Neale; David R. Haynes; Oksana T. Holubowycz; Margaret A. McGee; Lucian B. Solomon; Stuart A. Callary; Gerald J. Atkins; David M. Findlay (Inflammopharmacology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

5-Azacytidine as a tool to induce somaclonal variants with useful traits in sugarcane (Saccharum spp.) - Ashlin Munsamy; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (Plant Biotechnology Reports, 2013)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Environmental selection and resource allocation determine spatial patterns in picophytoplankton cell size - James R. Clark; Timothy M. Lenton; Hywel T. P. Williams; Stuart J. Daines (Limnology and Oceanography, 2013)
Here we describe a new trait‐based model for cellular resource allocation that we use to investigate the relative importance of different drivers for small cell size in phytoplankton. Using the model, we show that increased investment in nonscalable structural components with decreasing cell size leads to a trade‐off between cell size, nutrient and light affinity, and growth rate. Within the most extreme nutrient‐limited, stratified environments, resource competition theory then predicts a trend toward larger minimum cell size with increasing depth. We demonstrate that this explains observed trends using a marine ecosystem model that represents selection and adaptation of a diverse community defined by traits for cell size and subcellular resource allocation. This framework for linking cellular physiology to environmental selection can be used to investigate the adaptive response of the marine microbial community to environmental conditions and the adaptive value of variations in cellular physiology.

Cue reactivity in non-daily smokers - Saul Shiffman; Michael S. Dunbar; Thomas R. Kirchner; Xiaoxue Li; Hilary A. Tindle; Stewart J. Anderson; Sarah M. Scholl; Stuart G. Ferguson (Psychopharmacology, 2013)

In vitro generation of somaclonal variant plants of sugarcane for tolerance to Fusarium sacchari - Tendekai Mahlanza; R. Stuart Rutherford; Sandy J. Snyman; M. Paula Watt (Plant Cell Reports, 2013)

Big claims for big weights but with little evidence - Nicholas A. Burd; Daniel R. Moore; Cameron J. Mitchell; Stuart M. Phillips (European Journal of Applied Physiology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

Transcriptomics of coping strategies in free‐swimming Lepeophtheirus salmonis (Copepoda) larvae responding to abiotic stress - Ben J. G. Sutherland; Stuart G. Jantzen; Motoshige Yasuike; Dan S. Sanderson; Ben F. Koop; Simon R. M. Jones (Molecular Ecology, 2012)
The salmon louse Lepeophtheirus salmonis is a marine ectoparasite of wild and farmed salmon in the Northern Hemisphere. Infections of farmed salmon are of economic and ecological concern. Nauplius and copepodid salmon lice larvae are free‐swimming and disperse in the water column until they encounter a host. In this study, we characterized the sublethal stress responses of L. salmonis copepodid larvae by applying a 38K oligonucleotide microarray to profile transcriptomes following 24 h exposures to suboptimal salinity (30–10 parts per thousand ( ‰ )) or temperature (16–4 °C) environments. Hyposalinity exposure resulted in large‐scale gene expression changes relative to those elicited by a thermal gradient. Subsequently, transcriptome responses to a more finely resolved salinity gradient between 30 ‰ and 25 ‰ were profiled. Minimal changes occurred at 29 ‰ or 28 ‰ , a threshold of response was identified at 27 ‰ , and the largest response was at 25 ‰. Differentially expressed genes were clustered by pattern of expression, and clusters were characterized by functional enrichment analysis. Results indicate larval copepods adopt two distinct coping strategies in response to short‐term hyposaline stress: a primary response using molecular chaperones and catabolic processes at 27 ‰ ; and a secondary response up‐regulating ion pumps, transporters, a different suite of chaperones and apoptosis‐related transcripts at 26 ‰ and 25 ‰ . The results further our understanding of the tolerances of L. salmonis copepodids to salinity and temperature gradients and may assist in the development of salmon louse management strategies.

Conserved anchorless surface proteins as group A streptococcal vaccine candidates - Anna Henningham; Emiliano Chiarot; Christine M. Gillen; Jason N. Cole; Manfred Rohde; Marcus Fulde; Vidiya Ramachandran; Amanda J. Cork; Jon Hartas; Graham Magor; Steven P. Djordjevic; Stuart J. Cordwell; et al. (Journal of Molecular Medicine, 2012)

Eruption of kimberlite magmas: physical volcanology, geomorphology and age of the youngest kimberlitic volcanoes known on earth (the Upper Pleistocene/Holocene Igwisi Hills volcanoes, Tanzania) - Richard J. Brown; S. Manya; I. Buisman; G. Fontana; M. Field; C. Mac Niocaill; R. S. J. Sparks; F. M. Stuart (Bulletin of Volcanology, 2012)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

An in vitro mutagenesis protocol for the production of sugarcane tolerant to the herbicide imazapyr - Aimée C. Koch; Sumita Ramgareeb; R. Stuart Rutherford; Sandra J. Snyman; M. Paula Watt (In Vitro Cellular & Developmental Biology - Plant, 2012)

Multi-scale, object-based image analysis for mapping geomorphic and ecological zones on coral reefs - Stuart R. Phinn; Chris M. Roelfsema; Peter J. Mumby (International Journal of Remote Sensing, 2012)

A Chronological History of the International Conference on Cryptococcus and Cryptococcosis (ICCC), an Invaluable Forum for Growth of the Cryptococcal Research Field and Clinical Practice - Kyung J. Kwon-Chung; John R. Perfect; Stuart M. Levitz (Mycopathologia, 2012)

Response to “Comment on ‘Otolith Microchemistry Reveals Substantial Use of Freshwater by Southern Flounder in the Northern Gulf of Mexico’” by Pedro Morais - Michael R. Lowe; Stuart A. Ludsin; Brian J. Fryer; Russell A. Wright; Dennis R. DeVries; Troy M. Farmer (Estuaries and Coasts, 2012)

Genomic Resources for Sea Lice: Analysis of ESTs and Mitochondrial Genomes - Motoshige Yasuike; Jong Leong; Stuart G. Jantzen; Kristian R. von Schalburg; Frank Nilsen; Simon R. M. Jones; Ben F. Koop (Marine Biotechnology, 2012)

Similar increases in muscle size and strength in young men after training with maximal shortening or lengthening contractions when matched for total work - Daniel R. Moore; Mark Young; Stuart M. Phillips (European Journal of Applied Physiology, 2012)

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Multiple mechanisms underlie metastasis suppressor function of NM23-H1 in melanoma - Marian Novak; Stuart G. Jarrett; Joseph R. McCorkle; Isabel Mellon; David M. Kaetzel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2011)

Microdeletion/microduplication of proximal 15q11.2 between BP1 and BP2: a susceptibility region for neurological dysfunction including developmental and language delay - Rachel D. Burnside; Romela Pasion; Fady M. Mikhail; Andrew J. Carroll; Nathaniel H. Robin; Erin L. Youngs; Inder K. Gadi; Elizabeth Keitges; Vikram L. Jaswaney; Peter R. Papenhausen; Venkateswara R. Potluri; Hiba Risheg; et al. (Human Genetics, 2011)

Physiological consequences of military high-speed boat transits - Stephen D. Myers; Trevor D. Dobbins; Stuart King; Benjamin Hall; Ruth M. Ayling; Sharon R. Holmes; Tom Gunston; Rosemary Dyson (European Journal of Applied Physiology, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Near infrared spectroscopy-derived interstitial hydrogen ion concentration and tissue oxygen saturation during ambulation - Stuart M. C. Lee; Mark S. F. Clarke; Daniel P. O’Connor; Leah Stroud; Gwenn E. C. Ellerby; Babs R. Soller (European Journal of Applied Physiology, 2011)

Nutrient provision increases signalling and protein synthesis in human skeletal muscle after repeated sprints - Vernon G. Coffey; Daniel R. Moore; Nicholas A. Burd; Tracy Rerecich; Trent Stellingwerff; Andrew P. Garnham; Stuart M. Phillips; John A. Hawley (European Journal of Applied Physiology, 2011)

Multi-parameter flow cytometry and cell sorting reveal extensive physiological heterogeneity in Bacillus cereus batch cultures - Andrew Want; Helen Hancocks; Colin R. Thomas; Stuart M. Stocks; Gerhard Nebe-von-Caron; Christopher J. Hewitt (Biotechnology Letters, 2011)

An investigation into the preservation of microbial cell banks for α-amylase production during 5 l fed-batch Bacillus licheniformis fermentations - Nichola H. Hancocks; Colin R. Thomas; Stuart M. Stocks; Christopher J. Hewitt (Biotechnology Letters, 2010)

Auriacusite, Fe3+Cu2+AsO4O, the first M 3+ member of the olivenite group, from the Black Pine mine, Montana, USA - Stuart J. Mills; Anthony R. Kampf; Glenn Poirier; Mati Raudsepp; Ian M. Steele (Mineralogy and Petrology, 2010)

Structural characterisation of neutrophil glycans by ultra sensitive mass spectrometric glycomics methodology - Ponnusamy Babu; Simon J. North; Jihye Jang-Lee; Sara Chalabi; Kathryn Mackerness; Sean R. Stowell; Richard D. Cummings; Sara Rankin; Anne Dell; Stuart M. Haslam (Glycoconjugate Journal, 2009)

Potential contributions of antimutator activity to the metastasis suppressor function of NM23-H1 - David M. Kaetzel; Joseph R. McCorkle; Marian Novak; Mengmeng Yang; Stuart G. Jarrett (Molecular and Cellular Biochemistry, 2009)

The N-glycolyl form of mouse sialyl Lewis X is recognized by selectins but not by HECA-452 and FH6 antibodies that were raised against human cells - Junya Mitoma; Tatsuo Miyazaki; Mark Sutton-Smith; Misa Suzuki; Hideo Saito; Jiunn-Chern Yeh; Takehiro Kawano; Ole Hindsgaul; Peter H. Seeberger; Maria Panico; Stuart M. Haslam; Howard R. Morris; et al. (Glycoconjugate Journal, 2009)

Evaluation of the genetic variability of orchid fleck virus by single-strand conformational polymorphism analysis and nucleotide sequencing of a fragment from the nucleocapsid gene - Karen Sumire Kubo; R. M. Stuart; J. Freitas-Astúa; R. Antonioli-Luizon; E. C. Locali-Fabris; H. D. Coletta-Filho; M. A. Machado; E. W. Kitajima (Archives of Virology, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Threatened fishes of the world: Crystallaria cincotta Welsh and Wood 2008 (Percidae) - Stuart A. Welsh; Robert M. Wood; Kenneth R. Sheehan (Environmental Biology of Fishes, 2009)

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Historical reflections on the afterhyperpolarization–firing rate relation of vertebrate spinal neurons - E. K. Stauffer; J. C. McDonagh; T. G. Hornby; R. M. Reinking; D. G. Stuart (Journal of Comparative Physiology A, 2007)

Application of Predictive Distribution Modelling to Invertebrates: Odonata in South Africa - Jemma M. Finch; Michael J. Samways; Trevor R. Hill; Steven E. Piper; Stuart Taylor (Biodiversity and Conservation, 2006)

Glycomic studies of Drosophila melanogaster embryos - Simon J. North; Kate Koles; Caleb Hembd; Howard R. Morris; Anne Dell; Vladislav M. Panin; Stuart M. Haslam (Glycoconjugate Journal, 2006)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Measurement and nature of firing rate adaptation in turtle spinal neurons - R. B. Gorman; J. C. McDonagh; T. G. Hornby; R. M. Reinking; D. G. Stuart (Journal of Comparative Physiology A, 2005)

Afterhyperpolarization?firing rate relation of turtle spinal neurons - E. K. Stauffer; D. G. Stuart; J. C. McDonagh; T. G. Hornby; R. M. Reinking (Journal of Comparative Physiology A, 2005)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Increasing turbidity significantly alters the diet of brown trout: a multi‐year longitudinal study - R. D. Stuart‐Smith; A. M. M. Richardson; R. W. G. White (Journal of Fish Biology, 2004)
The stomach contents of adult brown trout Salmo trutta from Lake Sorell, Tasmania, were analysed during 6 years of increasing turbidity to follow changes in the diet associated with dramatic changes in water clarity. Brown trout were sampled from 1996, when turbidity was 26 NTU, to 2001 when turbidity was 141 NTU. The mean relative volume of stomach contents decreased progressively to 2001, by which time it was only one sixth of that in 1996, and the mean diversity of prey in stomachs decreased from an average of more than six species per stomach in 1996 to one species in 2001. The species composition of stomach contents shifted from domination by the phreatoicid isopod Colubotelson sp., to the galaxiid fish Galaxias auratus and the amphipod Austrochiltonia australis , and then the cladoceran Daphnia carinata . To give an indication of diet changes over a typical yearly cycle in the current turbid state of the lake, a sample was taken from each season from December 2000 to September 2001. Two basic diets were found during the year; brown trout specialized on D. carinata in summer and autumn, and G. auratus in winter and spring. Mean diversity of prey was less than two species per stomach in all samples from 2000 to 2001, except for the sample from spring 2001 when it was 2·2 species per stomach, and the mean relative volume of stomach contents was more than three times greater in winter than any other season. The ways in which high turbidity may have influenced the changes in the brown trout diet observed since 1996 and the patterns evident during the seasons of 2000–2001 are discussed.

Resistance to disuse atrophy in a turtle hindlimb muscle - J. C. McDonagh; R. J. Callister; M. L. Favron; D. G. Stuart (Journal of Comparative Physiology A, 2004)

Effects of fatigue on the catchlike property in a turtle hindlimb muscle - R. J. Callister; R. M. Reinking; D. G. Stuart (Journal of Comparative Physiology A, 2003)

Susceptibility to visceral leishmaniasis in the domestic dog is associated with MHC class II polymorphism - Rupert J. Quinnell; Lorna J. Kennedy; Annette Barnes; Orin Courtenay; Christopher Dye; Lourdes M. Garcez; Marie-Anne Shaw; Stuart D. Carter; Wendy Thomson; William E. R. Ollier (Immunogenetics, 2003)

A new human prostate carcinoma cell line, 22Rv1 - R. Michael Sramkoski; Thomas G. Pretlow; Joseph M. Giaconia; Theresa P. Pretlow; Stuart Schwartz; Man-Sun Sy; Susan R. Marengo; Johng S. Rhim; Desheng Zhang; James W. Jacobberger (In Vitro Cellular & Developmental Biology - Animal, 1999)

Past symposium attendees in the group photographs - Stuart R. Gelder; Susan M. Peterson (Hydrobiologia, 1999)

Outbreak of Escherichia coli O157 Infection Associated with a Music Festival - T. Cheasty; J. Stuart; M. Crampin; G. Willshaw; T. Djuretic; R. Hancock; C. Elstob; A. Rouse (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Salinity and fish effects on Salton Sea microecosystems: zooplankton and nekton - Cheryl M. Hart; Maria R. González; E. Paul Simpson; Stuart H. Hurlbert (Hydrobiologia, 1998)

Salinity and fish effects on Salton Sea microecosystems: benthos - E. Paul Simpson; Maria R. González; Cheryl M. Hart; Stuart H. Hurlbert (Hydrobiologia, 1998)

Salinity and fish effects on Salton Sea microecosystems: water chemistry and nutrient cycling - Maria R. González; Cheryl M. Hart; Joseph R. Verfaillie; Stuart H. Hurlbert (Hydrobiologia, 1998)

Resistance exercise training and the orthostatic response - John P. McCarthy; Marcas M. Bamman; Janice M. Yelle; Adrian D. LeBlanc; Roger M. Rowe; Michael C. Greenisen; Stuart M. C. Lee; Elisabeth R. Spector; Suzanne M. Fortney (European Journal of Applied Physiology, 1997)

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Notes on recent literature - W. Stuart; W. M. Peacock; W. S. Baird; W. Saxby Blair; R. H. Helmer; W. H. Hicks; W. R. Leslie; B. F. Lutman; H. H. Mann; S. D. Nagpurkar; G. S. Kulkarni; R. S. Kasargode; et al. (American Journal of Potato Research, 1924)

Preliminary seed certification notes - E. R. Dykeman; C. H. Hadley; W. A. McCubbin; Harold L. Bailey; O Butler; M. F. Barrus; R. F. Payne; N. W. Glimes; H. O. Werner; W. Stuart; Donald Folsom; W. H. M. (American Journal of Potato Research, 1923)